Green synthesis of biphenyl carboxylic acids via Suzuki–Miyaura cross-coupling catalyzed by a water-soluble fullerene-supported PdCl2 nanocatalyst. Issue 1 (January 2019) - Liu, Wanyun; Zhou, Xiuming; Huo, Ping; Li, Jingbo; Mei, Guangquan
A green synthesis of variously substituted biphenyl carboxylic acids was achieved through Suzuki–Miyaura cross-coupling of a bromobenzoic acid with an aryl boronic acid using a water-soluble fullerene-supported PdCl2 nanocatalyst (C60 -TEGs/PdCl2 ). Yields of more than 90% were obtained at room temperature in 4 h using 0.05 mol% catalyst and 2 equiv. K2 CO3 .